2020
DOI: 10.3389/fonc.2020.01349
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Correlation of Progression-Free Survival-2 and Overall Survival in Solid Tumors

Abstract: Background: Using progression-free survival (PFS)2, time from randomization to 2nd disease progression or death, is proposed as a surrogate for overall survival (OS) in oncology clinical trials. We used published data from solid tumor trials to assess whether PFS2 and OS are correlated. Methods: A literature search identified studies that reported PFS, PFS2, and OS. Two reviewers screened for eligibility, and documented PFS2, PFS or time from 1st to 2nd disease progression or death and OS. Correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
2
23
1
Order By: Relevance
“…In recent years, with the development of society, people's demand for spiritual life is increasing, the incidence of mental illness is also increasing year by year, and the incidence is mostly concentrated in big cities [ 11 13 ]. Modern medicine has a huge amount of complex data; in many cases, it is difficult to achieve a reasonable allocation of resources, which puts forward an urgent demand for the artificial intelligence of modern medicine and also brings great pressure to the development of the medical industry [ 14 16 ]. Compared with other kinds of diseases, the medical data of mental diseases may have more complex data records, which consumes a lot of medical human resources.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of society, people's demand for spiritual life is increasing, the incidence of mental illness is also increasing year by year, and the incidence is mostly concentrated in big cities [ 11 13 ]. Modern medicine has a huge amount of complex data; in many cases, it is difficult to achieve a reasonable allocation of resources, which puts forward an urgent demand for the artificial intelligence of modern medicine and also brings great pressure to the development of the medical industry [ 14 16 ]. Compared with other kinds of diseases, the medical data of mental diseases may have more complex data records, which consumes a lot of medical human resources.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of subsequent treatments may hide the effect of the first‐line treatment such that OS benefits are not always observed despite significant improvements in PFS. 22 Also imaginable is the scenario in which first‐line therapies may have a short PFS but extend OS by sensitizing tumor cells to second‐line agents. 23 In the current investigation, 69.6% of progressing males received D in the AA+ADT group as compared to 70.8% of those from the D+ADT group who received SHT upon progression.…”
Section: Discussionmentioning
confidence: 99%
“… 24 In a contemporary meta‐analysis of 15 studies on different tumor entities including PCa, Chowdhury and colleagues demonstrated that PFS2 strongly correlated with OS proposing its usage before OS data get mature or if OS cannot be assessed. 22 Using the data of the PROREPAIR‐B study which investigated the impact of germline DNA repair mutations on the outcomes of patients with mCRPC, 25 Lorente and coauthors observed that PFS2 outperformed PFS1 as a predictor of OS. Since the number of events during the second‐line treatment in our analysis was low precluding far‐reaching conclusions, further research is warranted to shed light on the influence of both AA+ADT and D+ADT on PFS2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One option that has been proposed is to consider time from randomization to second disease progression (PFS2). A meta-analysis showed a positive correlation for PFS2 and OS was found for all 15 studies that reported both endpoints, supporting the use of PFS2 to measure long-term clinical benefit when OS cannot be assessed [ 33 ]. However, in practice time to second progression may be difficult to monitor in a clinical trial.…”
Section: Do We Need An Innovation In Study Design and Is Overall Survmentioning
confidence: 96%